Incidence, prevalence, and risk factors for elbow and shoulder overuse injuries in youth athletes: A systematic review - Kraan, R. B. J.; de Nobel, D.; Eygendaal, D.; Daams, J. G.; Kuijer, P. P. F. M.; Maas, M. (Translational Sports Medicine, 2019)
Background: In order to create sport-specific preventive measures to enhance healthy sport participation in youth athletes, valid data on incidence, prevalence, and etiology of overuse injuries have to be identified. This systematic review aims to provide an update on incidence, prevalence, and risk factors for overuse injuries of the elbow and shoulder in youth athletes participating in overhead sports. Materials and Methods: MEDLINE and EMBASE were searched from inception until January 19, 2018, for studies that reported incidence, prevalence, or risk factors for overuse injuries or pain of the elbow and shoulder in youth overhead athletes. Results: In total, 36 studies were included. Incidence rates of overuse injuries of the elbow and shoulder were highest in tennis, baseball, and softball. Incidence and prevalence of elbow pain in baseball were 12%-58% and 17%-35%, respectively. Incidence of shoulder pain was 8%-32% for baseball, 47% for basketball, 63% for handball, and 52% for volleyball. Prevalence of shoulder pain was 9%-16% for baseball, 41% for basketball, 32%-49% for handball, and 40% for volleyball. Risk factors for pain were almost exclusively described for youth baseball players and included playing position, throwing technique, and intensity and duration of training. Conclusions: Incidence and prevalence of overuse injuries and pain of the elbow and shoulder are high in youth overhead athletes. Interpretation is challenging as different definitions are used to report overuse injuries and pain. Risk factors in youth baseball are largely covered by preventive pitch-count restrictions; knowledge on risk factors in other overhead sports is currently lacking.